Using BIM for assessing buildings life cycle impacts - Alecrim, Ismael (2020)
Facing the recent implementation of the Building Information Modelling (BIM) process in the construction industry, several potentialities have not been fully explored yet. Among them, is the integration of BIM in Life Cycle Assessment (LCA) analysis in order to automate the assessment of the potential environmental impacts. To date, despite the existing studies on the subject, there is still a need to define and establish a recommended assessment framework and software tool for LCA purposes when BIM methodology is used. This research analyses the current state of the implementation of the LCA analysis in the BIM process. Additionally, it compares the results from the use of two LCA software. For this purpose, a case study was modelled in the Autodesk Revit BIM platform and exported to two LCA specific BIM tools: Athena Impact Estimator and Tally. The life cycle impact results from both BIM tools, as well as the required workflows, are discussed and compared in order to validate results and identify the advantages and disadvantages of each. The results show that the implementation of the LCA method can be optimized in time and reliability by using the BIM process. Concerning the selected software, Tally has a better interoperability capability, userfriendly interface and a wider range of possible locations for the building. On the other hand, Athena Impact Estimator requires a detailed building characterisation to perform a comprehensive environmental impact assessment and has a broader materials database.